-6+6x-4x=16

Simple and best practice solution for -6+6x-4x=16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6+6x-4x=16 equation:


Simplifying
-6 + 6x + -4x = 16

Combine like terms: 6x + -4x = 2x
-6 + 2x = 16

Solving
-6 + 2x = 16

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 2x = 16 + 6

Combine like terms: -6 + 6 = 0
0 + 2x = 16 + 6
2x = 16 + 6

Combine like terms: 16 + 6 = 22
2x = 22

Divide each side by '2'.
x = 11

Simplifying
x = 11

See similar equations:

| x^2-4ax-2=0 | | -5x+7+2x=-8 | | 1=5x+3x-7 | | 1=p+12 | | 3*-2=5*4-26 | | -21n=483 | | 3sinx+4cosx^2=0 | | r+2=15 | | -3*-2=x+2 | | 2u+10=26 | | (2x-5)(3x+4)= | | 5x(63-16)= | | m^3-6=0 | | (4w-8)(w+3)=0 | | -2in(x)+in(y)=in(6) | | 6x^2-11x-13=5(x^2-1)+3 | | 8+6x=7x-5 | | V+4=-5 | | Y=-16x+20x+5 | | 3X^(7/3)-6=0 | | 5x^3=85 | | (4y-8)(3y+7)=0 | | w=mxf+eforx | | z(z+7)=0 | | 12x6/6x3 | | -4q-(-7.3)=45.9 | | 1x+.12x=34000 | | (X6)6/x3 | | 12x-8=14x-34 | | -3.6+2z=13.6 | | -3x+5y=34whenx+3y-18 | | 8(p+1)-8= |

Equations solver categories